Immune response and leukocyte profile in patients infested with Sarcoptes scabiei in Duhok Province of Kurdistan region, Iraq - Ahmed, Ahmed J; AL-Muffti, Shamal A; Najeeb, Malika K (The Journal of Infection in Developing Countries, 2025)
Introduction: Scabies is a skin condition that affects humans and many other mammalian hosts. It is brought on by the major obligate parasite Sarcoptes scabiei, which lives and reproduces in the epidermis and causes significant morbidity in both humans and animals. Methodology: The current study aimed to determine the immunological responses of 60 patients who were clinically infested with scabies and who attended the Department of Dermatology at Azadi Teaching Hospital and the Gulan General Hospital at Akre. Serum samples were tested to measure the levels of total immunoglobulin E (IgE), interleukin 4 (IL-4), interleukin 5 (IL-5), complement protein 3 (C3), and complement protein 4 (C4) in all patients with scabies; and compared with non-infested healthy individuals as a control group. A fresh blood sample from each patient was tested for total white blood cell (WBC) count, lymphocytes, monocytes, neutrophils, eosinophils and basophils. Results: The present study showed a significant increase in the mean of total WBCs and absolute eosinophil counts in patients infested with scabies when compared with controls (p ≤ 0.05). There were significant differences (p ≤ 0.05) in the mean of total IgE, IL4, Il-5, C3, and C4 serum levels in patients infested with scabies when compared with the controls. Non-significant differences (p < 0.05) were recorded for the other parameters that were measured. Conclusions: Scabies infection increased the levels of eosinophils and other immunological parameters, including IL4, Il-5, C3, C4, and total IgE.